Caring for Thai older persons with long-term care needs - KNODEL, John (Institutional Knowledge at Singapore Management University, 2018)
Objective: To provide a situation analysis of recent long-term care (LTC) needs among older persons in Thailand. Method: The 2014 Survey of Older Persons in Thailand (SOPT) provides data to assess patterns of caregiving,whether care needs are met, and who are main caregivers for older Thais. We examine how types of familial and non-familial caregivers are associated with the wellbeing of older persons. Results:The need for LTC increases sharply with age and is more common among women than men. Spouses and children constitute approximately 90% of main caregivers. The association of a family member as the main caregiver and education or value of assets is quite weak underscoring the general normative prescription for family members to serve as care providers. Discussion:Thailand is experiencing acute population aging but empirical evidence to support LTC needs remain slacking. This analysis helps close the gap.